COMPARATIVE EVALUATION OF MORPHOLOGICAL AND NUTRACEUTICAL TRAITS OF GENETICALLY MODIFIED TELA MAIZE AND OTHER MAIZE (Zea mays L.)VARIETIES IN LAFIA, NASARAWA STATE, NIGERIA (FULafia Journal of Science and Technology, 2026)
Maize (Zea mays L.) is one of the most significant cereal crops cultivated worldwide and serves as a staple food, animal feed, and industrial raw material. The research was carried out at the Botanical garden of the Federal University of Lafia to evaluate the morph-Nutraceutical compositions of different maize varieties cultivated in Nigeria. The experiment was laid out in a randomly complete block design (RCBD) with replications. Data collected were subjected to analysis of variance (ANOVA) using GenStat software version 18.0. All Morpho-Nutraceutical analysis and procedures were carried out according to AOAC. The result revealed that SAMMAZ 75 had the highest moisture content (9.378 %) while SAMMAZ 51 had the lowest moisture content (6.548 %). The (SAMMAZ 75 had the highest ash content (3.530 %) while SAMMAZ 51 had the least ash content (2.938 %). The % fat content varied significantly, with the highest value of 10.346 % observed in SAMMAZ 75 and the lowest value of 6.475 % in SAMMAZ 51. The percentage crude protein (C.P) ranged from 4.375 % SAMMAZ 52 to 10.937 % (SAMMAZ51). The percentage crude fibre (C.F) ranged from 4.935 % (SAMMAZ 34) to 8.328 % (SAMMAZ 75). The % carbohydrate (CHO) content ranged from 62.168 % SAMMAZ 75 to 70.082 % (SAMMAZ 34). Sammaz 34 sammaz 75 and sammaz 52 are therefore recommended for most of the agronomical, phytochemical and nutritional properties.Keywords: Morpho-nutraceutical, Genetically modify maize, Varieties
Keywords: Morpho-nutraceutical; Genetically modify maize; Varieties